PERANCANGAN APLIKASI BASE STATION DALAM SISTEM KOORDINASI ROBOT SEPAK BOLA BERODA DENGAN MULTI THREAD - Komang Edy Surya Prabowo; Yoga Divayana; Pratolo Rahardjo (Program Studi Teknik Elektro UNUD, 2022)
The Indonesian Wheeled Football Robot Contest (KRSBI Beroda) is one of the divisions of the Indonesian Robot Contest (KRI). At KRSBI Beroda robots are expected to be able to move automatically by using the Base Station as a communication center between robots in the same team. Base Station has a function to forward orders from the referee or RefBox (Referee Box) to the robot. This study aims to add features to the Base Station by displaying the position of two robots in the field in animation using the multi-thread method to facilitate strategy formulation. The result is that the Base Station that is made can display the position of two robots in the field without any errors.